Internationalizing multiculturalism : expanding professional competencies in a globalized world - Lowman, Rodney L. (Washington, D.C. : American Psychological Association, 2013)
'The concept of multiculturalism has been widely integrated into popular culture over the last half century. Yet the standard multicultural constructs - such as race, gender, sexual orientation, and religion - while still essential, are no longer adequate in today's increasingly globalized world. This book broadens the concept of multiculturalism to encompass internationalism. In other words, it internationalizes multiculturalism. It argues that professionals in all fields can enhance both their multicultural and international competence to perform more effectively. The contributors review the relevant research and, drawing also from personal experience, apply these concepts to real-world professional practice in business, mental health, and education - three areas that are especially well positioned to impact the health and well-being of clients, employees, and customers. This book will appeal to scholars of multiculturalism as well as practicing professionals in a range of fields, especially business, mental health, and education.' --From Publisher's Website.
Multicultural and international: Why and how both should matter in professional practice / Internationalizing multicultural issues: Race and ethnicity / Bringing gender into multicultural and international competencies: Strategies and challenges / National Origin, National Values, and Cultural Congruence / Sexually and Gender-Variant Individuals: International and Multicultural Perspectives / Religion, Spirituality, and Secularism in Multicultural and International Contexts / Fostering Multiculturally and Internationally Competent Individuals and Teams / Organizations in Multicultural and International Contexts: Insights for the Global Leader / The Multiculturally and Internationally Competent Mental Health Professional / Multicultural Education, Global Education: Synergies for a Peaceful World / Improving International Multicultural Competence by Working and Studying Abroad / Internationalizing Multiculturalism: Major Themes and Wrapping Up
Includes bibliographical references and index.
Keywords: Multiculturalism; Internationalism